Shedding Light on Three "Moral Cancer" Cases From the Czech Republic: Corruption in Communist and Post-Communist Regimes. (30th November 2022) - Plaček, Michal; Ochrana, František; Vaceková, Gabriela; Langr, Ivan; Půček, Milan
Abstract: Using a new and innovative approach to investigating corruption, the present article discusses whether changes have been recorded in corruption in the Czech Republic over the last hundred years. Drawing on a historical-evolutionary view of corruption, the article seeks to cover a research gap in the legacies of corruption in post-communist economies. The qualitative methodological approach provides deep insight into the researched issue through confidential information related to three major corruption cases from different periods. The article argues that the transformation of corruption under the Communist and post-Communist governments in Czechoslovak and Czech society may be explained from inherited-historical, ontological, and moral-framing perspectives, as well other perspectives, and it provides an overview and explanation of changes in corruption. The major policy implication is that understanding the development of corruption highlights the importance of designing an effective public policy against corruption in post-communist countries.